2007
DOI: 10.4049/jimmunol.178.3.1261
|View full text |Cite
|
Sign up to set email alerts
|

Activating Ly-49 Receptors Regulate LFA-1-Mediated Adhesion by NK Cells

Abstract: NK cells are important for innate resistance to tumors and viruses. Engagement of activating Ly-49 receptors expressed by NK cells leads to rapid NK cell activation resulting in target cell lysis and cytokine production. The ITAM-containing DAP12 adapter protein stably associates with activating Ly-49 receptors, and couples receptor recognition with generation of NK responses. Activating Ly-49s are potent stimulators of murine NK cell functions, yet how they mediate such activities is not well understood. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…By contrast, for Th2 cells that do not have such defined monocentric synapses, TCR signalling appears to last longer -that is, it is not so rapidly extinguished in the cSMAC. Granule-releasing NK cells also have monocentric synapses where LFA-1 forms a peripheral ring around a central cluster of receptors (Osman et al, 2007).…”
Section: Interactions Between Leukocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, for Th2 cells that do not have such defined monocentric synapses, TCR signalling appears to last longer -that is, it is not so rapidly extinguished in the cSMAC. Granule-releasing NK cells also have monocentric synapses where LFA-1 forms a peripheral ring around a central cluster of receptors (Osman et al, 2007).…”
Section: Interactions Between Leukocytesmentioning
confidence: 99%
“…This is necessary to prevent dephosphorylation of key kinases such as ZAP-70, thus maintaining signalling. Other leukocytes such as B cells (Carrasco et al, 2004) and natural killer (NK) cells (Osman et al, 2007) also form the classical bull's-eye IS when encountering their targets. For B cells, adhesion to ICAM1 recruits LFA-1 into a peripheral ring as it does with T cells, and this interaction lowers the affinity of binding between the BCR and antigen that is needed to trigger B-cell activation (Carrasco et al, 2004).…”
Section: Interactions Between Leukocytesmentioning
confidence: 99%
“…The binding activity of integrins is mediated by inside-out signaling, where signals of other activating receptors increase integrin binding affinity by adopting an extended conformation of extracellular domains of the integrins (5,6). It was shown that different activating NK cell receptors harbor the potential to induce the high-affinity conformation of LFA-1 (8,9). The inside-out signaling has mostly been studied in T cells and was shown to involve PKC, talin, the small GTPases Ras and Rap1, as well as an association of actin with LFA-1 (10).…”
mentioning
confidence: 99%
“…Similar to naive CD8 ϩ T cells, recall responses by memory CD8 ϩ T cells to previously encountered Ags require the presence of DCs (31). Cell-sized microspheres have been successfully used to investigate the role of immobilized protein ligands on lymphocyte activation and/or adhesion (32)(33)(34)(35)(36)(37). Substitution of microspheres for DCs allows for the precise control of the constellation and density of ligands displayed to a responding CD8 ϩ T cell.…”
mentioning
confidence: 99%